Why We Can Thrive past Seventy-Five: In Favor of Efforts to Extend the Human Lifespan - Ringel, Carolyn B. (The Hastings Center report, 2025)
About ten years ago, Ezekiel Emanuel wrote an article extolling the benefits of dying at seventy-five. Since then, longevity and aging interest, research, and funding have exploded. Much of the public is supportive of aging biology research, and books on extending the human lifespan populate bestseller lists. However, the issue remains hotly debated, and many articles published in the lay press spin the research in a negative light. Yet, if we collect these arguments and address each one logically, we see that each implies untenable conclusions. More to the point, there are strong arguments that human health and life have fundamental value and that incremental gains in health and in years of life will benefit us. For both ethical and practical reasons, we should support aging research.